Application and violation of politeness maxims used by President Biden’s speech: A pragmatics analysis - Pramudita Ariani; Widyashanti Kuntara Anindita (Jurnal CULTURE (Culture, Language, and Literature Review), 2024)
Abstract This research analyses the application and violation of the Politeness Principle in Maxims used by President Joe Biden's speech using Geoffrey Leech's politeness theory approach. This research aims to identify what is the dominant relationship between the application and violation of the maxim of politeness in President Biden's speech regarding the Israeli-Palestinian conflict and what are the reasons for the application or violation which can have an impact on public perception. This research uses descriptive qualitative analysis methods. The data collected is analysis based on Leech's politeness principles theory concepts to identify the applications and violations of politeness principle in Maxims used by President Biden's speech. The results indicate an insignificant use of Leech's politeness principles due to the political cooperation between the United States and Israel, so that President Biden frequently violates the principle of politeness in his speeches. However, in several utterances President Biden applies the politeness principle to maintain his image towards public perception. Keywords: Speech, Leech's Politeness Principle, and Maxim.